A Paradigm Shift: Adoption of Disruptive Learning Innovations in an ODL Environment: The Case of The University of South Africa - Mbatha, Blessing (International Review of Research in Open and Distributed Learning, 2015)
The aim of this article is to shed some light on patterns of and major motives for the adoption of different types of disruptive learning innovations by Unisa academics. To realise the aim of the study, the following questions were addressed: What are the reasons for adopting disruptive learning innovations? What is the level of interaction with disruptive innovations? What training do Unisa academics require on disruptive innovations? A qualitative approach was adopted by conducting focus group interviews with 76 Unisa academics. The data was analysed using open and axial coding, where dominant themes from the discussions were identified and discussed in detail. The findings show that the interaction of Unisa lecturers with different technologies varied from technology to technology. The study also found that disruptive innovations play a pivotal role in opening avenues and collapsing the transactional distance in an ODL institution. Some lecturers lack skill in using some technology, which is a cause for concern. Therefore, lecturers need to be trained in using technology and develop a good understanding of it to improve teaching and learning.